ILC-You in the Thymus: A Fresh Look at Innate Lymphoid Cell Development - Shin, Samuel B.; McNagny, Kelly M. (Frontiers in Immunology, 2021)
The discovery of innate lymphoid cells (ILCs) has revolutionized our understanding of innate immunity and immune cell interactions at epithelial barrier sites. Their presence and maintenance are critical for modulating immune homeostasis, responding to injury or infection, and repairing damaged tissues. To date, ILCs have been defined by a set of transcription factors, surface antigens and cytokines, and their functions resemble those of three major classes of helper T cell subsets, Th1, Th2 and Th17. Despite this, the lack of antigen-specific surface receptors and the notion that ILCs can develop in the absence of the thymic niche have clearly set them apart from the T-cell lineage and promulgated a dogma that ILCs develop directly from progenitors in the bone marrow. Interestingly however, emerging studies have challenged the BM-centric view of adult ILC development and suggest that ILCs could arise neonatally from developing T cell progenitors. In this review, we discuss ILC development in parallel to T-cell development and summarize key findings that support a T-cell-centric view of ILC ontogeny.